Permit markets, carbon prices and the creation of innovation clusters - Hans Gersbach; Marie-Catherine Riekhof (ETH Zurich, CER-ETH - Center of Economic Research, 2018)
Innovation clusters combining public and private effort to develop breakthrough technologies promise greater technological advances to slow down climate change. We use a multi-country model with emissions permit trade to examine how international climate policy can incentivize countries to create such clusters. We find that a minimal carbon price is needed to attract applied research firms, but countries may nevertheless fail to invest in complementary research infrastructure. We construct a mechanism that leads to innovation clusters. It is a combination of low permit endowments for the country with the lowest costs to build the needed infrastructure, compensation for this country by profits from permit trade, and maximal possible permit endowments for the remaining countries.
Keywords: H23; Q54; O32; 330; International permit markets; Carbon prices; Innovation clusters; Research infrastructure; Applied R&D; Climate change mitigation; Externalities